Elevated Soluble CD14 and Lower D-Dimer Are Associated With Cigarette Smoking and Heavy Episodic Alcohol Use in Persons Living With HIV. (1st December 2015) - Cioe, Patricia A.; Baker, Jason; Kojic, Erna M.; Onen, Nur; Hammer, John; Patel, Pragna; Kahler, Christopher W.
Abstract : Background: Persons living with HIV are at increased risk for cardiovascular disease in part because of persistent inflammation and coagulation activation. Methods: We examined whether smoking and heavy episodic alcohol use (defined as 5 or more drinks on one occasion) were associated with greater monocyte activation (soluble CD14) and coagulation (D-dimer) in participants in the Study to Understand the Natural History of HIV and AIDS in the Era of Effective Therapy (the "SUN" Study), a prospective observational cohort. Results: Using regression analysis (n = 689), current smoking compared with nonsmoking was associated with significantly elevated soluble CD14 (B = 135.57, 95% confidence interval: 84.95 to 186.19, P < 0.001), whereas heavy alcohol use compared with nonheavy use was associated with significantly lower D-dimer levels (B = −0.059, 95% confidence interval: −0.102 to −0.016, P = 0.007). Conclusions: Smoking cessation should be encouraged by HIV care providers to improve mortality outcomes from all causes of death, particularly cardiovascular disease.